Methylotroph bacteria and cellular metabolite carotenoid alleviate ultraviolet radiation-driven abiotic stress in plants - Mohanty, Santosh Ranjan; Mahawar, Himanshu; Bajpai, Apekcha; Dubey, Garima; Parmar, Rakesh; Atoliya, Nagvanti; Devi, Mayanglambam Homeshwari; Singh, Amar Bahadur; Jain, Devendra; Patra, Ashok; Kollah, Bharati (Frontiers in Microbiology, 2023)
Increasing UV radiation in the atmosphere due to depletion of ozone layer is an emerging abiotic stress for agriculture. Although plants have evolved to adapt to UV radiation through different mechanisms, but the role of phyllosphere microorganisms in counteracting UV radiation is not well studied. The current experiment was undertaken to evaluate the role of phyllosphere Methylobacteria and its metabolite in the alleviation of abiotic stress rendered by ultraviolet (UV) radiation. A potential pink pigmenting methylotroph bacterium was isolated from the phylloplane of the rice plant (oryzae sativa). The 16S rRNA gene sequence of the bacterium was homologous to the Methylobacter radiotolerans. The isolate referred as Methylobacter radiotolerans strain N39, produced beta carotene at a rate (µg mL-1 d-1) of 0.45 to 3.09. Biosynthesis of beta carotene was stimulated by brief exposure to UV for 10 min per 2 days. Carotenoid biosynthesis was predicted as y = 3.09 x incubation period + 22.151 (r² 0.90). The carotenoid extract of N39 protected the E. coli from UV radiation by declining its death rate from 14.67 % min-1 to 4.30 % min-1 under UV radiation. Application of N39 cells and carotenoid extract also protected rhizobium (Bradyrhizobium japonicum) cells from UV radiation. Scanning electron microscopy indicated that the carotenoid extracts protected E. coli cells from UV radiation. Foliar application of either N39 cells or carotenoid extract enhanced the plant’s (Pigeon pea) resistance to UV irradiation. This study highlight that M. radiotolerans N39 and its carotenoid extract can be explored to manage UV radiation stress in agriculture.